Generation Z’s Perspectives and Responses to Climate Change: The Role of Education and Social Media - Yanuar Luqman; Muhammad Bayu Widagdo (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
This study aims to analyze Generation Z's perspectives on climate change and to describe their patterns of understanding and response to this issue, including how they acquire information, interpret the impacts of climate change, and take action in their daily lives. Additionally, this study evaluates the role of educational institutions and social media in shaping awareness and provides recommendations to enhance their engagement in environmental issues. A quantitative descriptive approach was employed, utilizing online surveys, interviews, and focus group discussions to collect data from respondents across various regions. The findings indicate that Generation Z has a high level of awareness regarding climate change and recognizes human activities as the primary cause. They actively seek information through social media, particularly Instagram, and gain further understanding from educational institutions. Visual educational content and support from educators contribute to shaping their attitudes and concrete actions, such as reducing plastic and energy consumption, to promote environmental sustainability.